Analisis Dilālah al-Mafhūm al-Mukhālafah dalam Ushul Fiqh dan Relevansinya terhadap Istinbath Hukum Islam Kontemporer - Abd. Rahman; Fatmawati Fatmawati; Abd. Syatar (Lembaga Yasin AlSys, 2026)
Mafhūm al-mukhālafah is one of the methods of legal derivation in uṣūl al-fiqh used to understand the implicit meaning of a scriptural text through an opposite interpretation of the wording stated. Although it has long been part of classical uṣūl al-fiqh studies, debates regarding its probative authority and relevance in addressing contemporary Islamic legal issues continue to persist. This study aims to analyze the concept, probative authority, and relevance of mafhūm al-mukhālafah in the process of contemporary Islamic legal derivation. This study used a qualitative approach with a library research design. Data were obtained through documentation studies of classical uṣūl al-fiqh texts, scientific articles, books, and contemporary literature discussing mafhūm al-mukhālafah and its application in modern Islamic law. The data were analyzed descriptively and analytically by examining the concept, scholarly arguments, and developments in its use across various contemporary issues. The results show that mafhūm al-mukhālafah has strong methodological legitimacy, particularly within the Shafi‘i school tradition, as an instrument for understanding the implicit meaning of scriptural texts. Its use in contemporary contexts has developed through integration with the maqāṣid al-syarī‘ah approach, making it relevant in responding to legal issues related to the digital economy, electronic transactions, and modern technological developments. This study also found differences in scholarly views regarding the probative authority of mafhūm al-mukhālafah, which are influenced by differing textual and contextual paradigms in legal derivation. The conclusion of this study affirms that mafhūm al-mukhālafah remains relevant as a methodological instrument in the development of contemporary Islamic law when used proportionally and integrated with the principles of maqāṣid al-syarī‘ah. The contribution of this study lies in strengthening an uṣūl al-fiqh methodology that is adaptive to social change without disregarding the normative foundations of sharia.